1989
DOI: 10.1111/j.1440-6055.1989.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Biology of Acrodzpsas Zllzdgez (Waterhouse and Lyell), a Myrmecophagous Lycaenid (Lepidoptera: Lycaenidae: Theclinae)

Abstract: Acrodipsas illidgei (Waterhouse and Lyell) has mynnecophagous larvae associated with the ant Crematoguster sp. (laeviceps group). Eggs were found on the trunk and branches of the mangrove Avicennia marina colonised by the host ant. Two types of epidermal organs, possibly glandular, were identified in first instar larvae, and a Newcomer's organ was present from the second instar onwards. Biology was observed in artificial ant colonies. First instar larvae were camed by the ants and placed near the ant brood whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Sands (1980); Samson (1987) Hutchings & Recher (1982); Hutchings & Saenger (1987); Samson (1989Samson ( , 1993; Beale (1995Beale ( , 1997; Beale & Zalucki (1995) [E] [Papyrius nitidus] Waterhouse (1941a);D'Abrera (1971). Sands (1980); Samson (1987) Hutchings & Recher (1982); Hutchings & Saenger (1987); Samson (1989Samson ( , 1993; Beale (1995Beale ( , 1997; Beale & Zalucki (1995) [E] [Papyrius nitidus] Waterhouse (1941a);D'Abrera (1971).…”
Section: Categorization Of Ant Attendance Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Sands (1980); Samson (1987) Hutchings & Recher (1982); Hutchings & Saenger (1987); Samson (1989Samson ( , 1993; Beale (1995Beale ( , 1997; Beale & Zalucki (1995) [E] [Papyrius nitidus] Waterhouse (1941a);D'Abrera (1971). Sands (1980); Samson (1987) Hutchings & Recher (1982); Hutchings & Saenger (1987); Samson (1989Samson ( , 1993; Beale (1995Beale ( , 1997; Beale & Zalucki (1995) [E] [Papyrius nitidus] Waterhouse (1941a);D'Abrera (1971).…”
Section: Categorization Of Ant Attendance Levelmentioning
confidence: 99%
“…Crematogaster sp. Sands (1980); Samson (1987) Hutchings & Recher (1982); Hutchings & Saenger (1987); Samson (1989Samson ( , 1993; Beale (1995Beale ( , 1997; Beale & Zalucki (1995) [E] [Papyrius nitidus] Waterhouse (1941a); D'Abrera (1971). A. illidgei was later found to be distinct from the lycaenid subspecies referred to by Waterhouse (1941a) (see Kerr et al 1968) New (1987New ( , 1991; E&F (96.006) H N. capitatus Vaughan (1987Vaughan ( , 1988; Braby (1990); New (1993); Endersby (1996); van Praagh (1996) H N. ectatommoides Vaughan (1987Vaughan ( , 1988; Braby (1990); New (1993); van Praagh ( Barrett & Burns (1951, 1966; Common (1964); Macqueen (1965); McCubbin (1971) (1972,1981).…”
mentioning
confidence: 99%
“…It has been observed that individual larvae integrated into ant cultures spend on average 18% of time actively secreting droplets and that attendant host ants drink secretions from the caterpillars for 53% time; unattended caterpillars glistened with accumulated droplets (Elmes et al, 1991). Furthermore, some other lycaenid social parasites have a large functional dorsal nectary organ (Samson, 1989;Nomura et al, 1992;Sanetra & Fiedler, 1996;Eastwood & King, 1998). Thus although Maculinea larvae undoubtedly inflict great damage on the cohort of ant larvae with which they compete or on which they prey (Elmes et al, 1991;Thomas & Wardlaw, 1992), we questioned whether they might also retain some vestige of the ancestral mutualism by recycling food (particularly sugars) to the worker ants, which might in turn enhance the fitness of the host workers when other sources of sugar were in short supply.…”
Section: Introductionmentioning
confidence: 99%
“…Samson 1987Samson , 1989, although the presence of apparently trophallactic type behaviours, observed once by Samson (1989), and many times during our study, implies that the larva's diet is supplemented by ant regurgitations, reducing the pressure on ant brood supplies. Gooding (1971) suggested that the early larval instars of A .…”
Section: Discussionmentioning
confidence: 65%
“…(laeviceps group), as recorded by Samson (1987Samson ( , 1989. These ants were ubiquitous throughout all areas surveyed.…”
Section: Occurrence Ofmentioning
confidence: 99%